MICROBIOLOGICAL OF BALI BEEF MARINED WITH DIFFERENT CONCENTRATIONS OF MORINGA LEAF POWDER (Moringa oleifera Lamk) - I P. G. S., RAGAWARDANA; SRIYANI, N. L. P.; WIBAWA, A. A. P. P. (Majalah Ilmiah Peternakan; Vol 26 No 1 (2023): Vol. 26 No. 1 (2023)DO - 10.24843/MIP.2023.V26.i01.p06, 2023)
This study aimed to investigate the effect of marinating with Moringa leaf powder solution with different con- centrations on microbiological of Bali beef stored at room temperature for 12 hours. The experimental design used was a completely randomized design (CRD) with four treatments and four replications. Each replication consisted of 100 g of beef. The four treatments were: P0 (Bali beef marinated in 0% solution of Moringa leaf powder), P1 (0.2% w/v solution of Moringa leaf powder), P2 (0.4% w/v solution of Moringa leaf powder), P3 (0.6% w/v solution of Moringa leaf powder). The variables observed in this study were the Total Plate Count (TPC), Total Coliform and Escherichia coli, the pH value, and the water content of the meat. The results showed that the treatment of Moringa leaf powder had a significant effect (P<0.05) on microbiological of Bali beef. The conclusion of this study is that the marinated solution of Moringa leaf powder affects the microbiological quality of Bali beef, which reduces the Total Plate Count (TPC), but has no effect on total Coliform, Escherichia coli, water content, and pH levels. Total Plate Count, Coliform, Escherichia coli, and all treatments were above the SNI threshold. It means that Bali beef mari- nated with concentrations of 0% (P0), 0.2% (P1), 0.4% (P2), and 0.6% (P3) and stored at room temperature for 12 hours is not suitable for consumption.